Men and the Classroom - Drudy, Sheelagh (Taylor & Francis, 2005)
The teaching of young children has long been dominated by women. This global phenomenon is firmly rooted in issues related to economic development, urbanization, the position of women in society, cultural definitions of masculinity and the values of children and childcare. Yet, amongst the media scare stories and moral panics about underachieving boys, there are surprisingly few empirically-supported answers to vital questions such as: Is the feminisation of teaching really a problem? How is the relationship of gender and teaching considered within a framework of feminist theory? What are the perceptions of students of teaching, in comparison to other professions? Why are so few men attracted to teaching? Can more men be attracted into the classroom? The authors of this groundbreaking book have undertaken the largest, most in-depth study ever carried out on this topic, in order to assess both teachers and students' views across primary education.